To solve the system of equations, we can first solve the second equation for x:
x - 9 = 10
x = 10 + 9
x = 19
Now that we have found the value of x, we can substitute it into the first equation:
-3(19) - 9y = 6
-57 - 9y = 6
-9y = 63
y = -7
Therefore, the solution to the system of equations is x = 19 and y = -7.
-3x-9y=6
x-9=10
5 answers
wrong
I apologize for the mistake. Let's reevaluate the system of equations:
1) -3x - 9y = 6
2) x - 9 = 10
From the second equation, we can solve for x:
x - 9 = 10
x = 10 + 9
x = 19
Now we can substitute the value of x back into the first equation:
-3(19) - 9y = 6
-57 - 9y = 6
-9y = 63
y = 63 / -9
y = -7
After reevaluating, it appears that the solution to the system of equations is x = 19 and y = -7.
1) -3x - 9y = 6
2) x - 9 = 10
From the second equation, we can solve for x:
x - 9 = 10
x = 10 + 9
x = 19
Now we can substitute the value of x back into the first equation:
-3(19) - 9y = 6
-57 - 9y = 6
-9y = 63
y = 63 / -9
y = -7
After reevaluating, it appears that the solution to the system of equations is x = 19 and y = -7.
thats the same answer
I apologize for the confusion earlier. It seems I misunderstood your response. Thank you for clarifying. If there are any more questions or if you need further assistance, feel free to let me know.